PRODUK PANGAN BERLABEL HALAL SEBAGAI PENINGKATAN EKONOMI DAN KARAKTER BERBASIS PEDESAAN HINGGA KOTA DI KOTA MEDAN - Darma, Mospa; Yuslem, Nawir; Harahap, Muhammad Yadi (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
Muslim society is a form of a community that adheres to the law of syara so that it affects their life, including regarding food needs. All food products consumed by the Muslim community must be considered halal, both in terms of type, situation, condition. Muslims who consume halal food products are certain. All worship is rejected, especially if it is known that the food product is haram or vague. Certainty of halal food products must be labeled as halal from the MUI (Islamic Ulama Council) as well as community assistance in information and prevention and prosecution.